How a multi-cloud strategy enables digital transformation - Balala, Maliha (O'Reilly Media, 2018)
Having spent an estimated $1.2 trillion in 2017 alone, industries today are investing heavily in digital transformation technologies. Cloud providers are a key part of the investment, but many companies are finding that no single provider can meet the specific needs of every business. In this article, author Maliha Balala explains how a growing number of companies are covering all the bases by engaging more than one cloud provider. By choosing a multi-cloud approach, you can mix and match technologies and services from different providers to create the best possible solution for your company. Whether you want to spread workloads and data across multiple cloud platforms, mitigate risk, or enable specific business units to choose their ideal cloud service, this article shows you how this approach can help you migrate from your old model of customer engagement to a newer, digital-based strategy.